2019
DOI: 10.1002/mus.26736
|View full text |Cite
|
Sign up to set email alerts
|

Deflazacort vs prednisone treatment for Duchenne muscular dystrophy: A meta‐analysis of disease progression rates in recent multicenter clinical trials

Abstract: Introduction: In this study we characterized disease progression over 48 weeks among boys receiving deflazacort vs prednisone/prednisolone placebo arm treatment in two recent Duchenne muscular dystrophy (DMD) clinical trials.Methods: Ambulatory boys with DMD receiving placebo in the phase 3 ataluren (N = 115) and tadalafil (N = 116) trials were included. The trials required at least 6 months of prior corticosteroid use and stable baseline dosing. Associations between corticosteroid use and 48-week changes in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 27 publications
2
43
0
3
Order By: Relevance
“…[6][7][8] Regarding pharmacological treatment, the corticosteroids deflazacort and prednisone/prednisolone are the gold standard of treatment, as they slow disease progression. 9 Ataluren is known to slow disease progression versus placebo in DMD patients with nonsense mutations, most evident in patients with a baseline 6-minute walk test (6MWT) !300 m to <400 m. 10 Eteplirsen is a therapeutic drug for DMD patients with special mutations, that can be overridden by skipping exon 51 of the DMD gene. Eteplirsen showed evidence of muscle cell penetration, exon skipping, and induction of novel dystrophin expression.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Regarding pharmacological treatment, the corticosteroids deflazacort and prednisone/prednisolone are the gold standard of treatment, as they slow disease progression. 9 Ataluren is known to slow disease progression versus placebo in DMD patients with nonsense mutations, most evident in patients with a baseline 6-minute walk test (6MWT) !300 m to <400 m. 10 Eteplirsen is a therapeutic drug for DMD patients with special mutations, that can be overridden by skipping exon 51 of the DMD gene. Eteplirsen showed evidence of muscle cell penetration, exon skipping, and induction of novel dystrophin expression.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been undertaken to investigate the use of biomarkers in DMD [ 17 , 18 , 19 ] and the efficacy and safety of Pred versus Dfz [ 10 , 11 , 12 , 20 , 21 ]. Both drugs are known to be efficacious in prolonging ambulation [ 10 , 11 , 14 , 22 ]. For our purposes here, we provide a small review on safety comparisons from the literature.…”
Section: Introductionmentioning
confidence: 99%
“…There are ongoing debates among families, clinicians, and regulatory agencies over which GC drug (Pred or Dfz) and regimen is better for DMD boys. GC responsive biomarkers (for both safety and efficacy) have been defined and confirmed in different diseases and multiple cohorts [ 17 , 24 , 25 ], using data with pooled corticosteroid drugs not differentiating between Pred and Dfz and different regimens [ 22 ]. However, much remains unknown about the comparative effects of Pred vs. Dfz on blood accessible biomarkers and how they can inform clinical decision-making and drug development.…”
Section: Introductionmentioning
confidence: 99%
“…A post-hoc analysis from 421 the placebo arm of the DMD ACT trial (ataluren) 422 reported patients on deflazacort had improved 6 423 minute walk distances (6MWD) and 4 stair climb 424 times (4SCT) compared to prednisone [125]. A sim-425 ilar post hoc analysis from the placebo groups of the 426 phase 3 ataluren trial and tadalafil studies (N = 231) 427 showed that deflazacort improved 6MWD and rise-428 from-supine time significantly more than prednisone, 429 while no difference was found in 10-meter run and 430North Star Ambulatory Assessment (NSAA) scores between the steroid treated groups[126]. A retro-benefits with fewer side effects and no change in quality of life (N = 17), although the study lacked a daily treated control cohort[129].…”
mentioning
confidence: 99%